Political Context of Celebrations of Anniversaries of the Constitutional Assembly, 1927–1940 (Parliamentary Studies, 2020)
The article examines the political circumstances in which the anniversaries of the Constituent Assembly were celebrated after the coup d’etat of 1926. The means by which the political regime tried to undermine the links between the „national holiday“ and the origins of parliamentary democracy are analyzed. Attempts to change May 15 as a „nation’s holiday“ into December 17 did not catch on and antagonized the public. Thus the regime was forced to leave May 15 as an official holiday, but had to change its content. During 1927–1940, gradually the Day of the Constituent Assembly evolved into a celebration of the Rapprochement of the Armed Forces and the Society (1935–1937) and the official Holiday of the Armed Forces and the Society (1938–1940).The commemoration of May 15 is described as the disputed political process between supporters of political pluralism and the one-party regime. The article examines the difficulties encountered in trying to organize festive events and how the interpretation of this date, presented by left-wing parties, Christian Democrats, Nationalists, and non-political organizations, has changed. Attention is drawn to the attempts of the Nationalists to popularize the 17th of December of 1926 as a symbolic beginning of the „second revival of the Lithuanian nation“. The article also describes the last commemorations of public holidays and their symbolic meaning in independent Lithuania in 1940.
Keywords: Constituent Assembly; „Nations’s Day“; May 15; December 17; Lithuanian political parties